Re-Employment Bonuses in a Signalling Model of Temporary Layoffs - Núria Rodríguez-Planas (Institute for the Study of Labor (IZA), 2004)
Temporary layoffs are an important feature of the United States labor market. If these employer-employee relationships exist because of valuable job-matches, unemployment among high-productivity laid-off workers may be optimal from societal perspective. However, because of asymmetric information, low-productivity workers may behave strategically, and choose unemployment instead of low-wage jobs, resulting in an inefficient level of unemployment. This paper shows that in such cases, a re-employment bonus may give the correct incentives to laid-off workers and achieve the optimal equilibrium. The paper analyzes the equity properties of such a policy and its cost effectiveness. Finally, the model fits the data and offers several policy implications.
Keywords: J63; J65; J64; 330; temporary layoffs; recall expectations; unemployment; signalling and re-employment bonus demonstrations; Friktionelle Arbeitslosigkeit; Arbeitsproduktivität; Signalling; Arbeitsmarktpolitik; Arbeitsuche; Theorie